2014
DOI: 10.1074/jbc.m114.562785
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Changes in Phosphorylation and Methylation of Mammalian Brain Sodium Channels in Response to Seizures

Abstract: Background: Sodium channels underlie neuronal excitability and are regulated by seizures. Results: Mass spectrometric analysis of brain sodium channels revealed novel phosphorylation and methylation sites that decreased and increased, respectively, after seizures. Inducing methylation increased sodium channel activity. Conclusion: Reciprocal phosphorylation and methylation after seizures will alter sodium channel function. Significance: Such regulation would impact neuronal excitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 53 publications
(52 reference statements)
3
62
0
Order By: Relevance
“…phosphorylation-dependent regulation of channel activity (Surti et al, 2005;Baek et al, 2014;Verdoucq et al, 2014). Based on these results, we hypothesized that phosphorylation of amino acids in the transmembrane domain causes SLAC1 activation in the CO 2 response and performed site-directed mutagenesis experiments with transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…phosphorylation-dependent regulation of channel activity (Surti et al, 2005;Baek et al, 2014;Verdoucq et al, 2014). Based on these results, we hypothesized that phosphorylation of amino acids in the transmembrane domain causes SLAC1 activation in the CO 2 response and performed site-directed mutagenesis experiments with transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…104 Beyond studies of individual PTMs, advances have been made in the study of interactions between PTMs. Baek et al 105 described downregulated phosphorylation of the brain sodium channel Nav1.2 after kainite-induced seizures with concomitant upregulated methylation at adjacent sites, which suggested reciprocal regulation of these 2 PTMs. In the specific context of histones, Garske and colleagues 104 used a MALDI-TOF (matrix-assisted laser desorption/ionization TOF) MS approach to demonstrate novel chromatin phosphorylation and methylation sites that interact with each other and mediate binding of chromatin binding proteins such as histone H3.…”
Section: The Promise Of Proteomicsmentioning
confidence: 99%
“…Ion channels, especially voltage-gated channels, are critically regulated by phosphorylation. Voltage-dependent sodium and potassium channels have been shown to be the target of multiple phosphorylation events, regulating different channel functions and being involved in pathological states, like epilepsy (7)(8)(9)(10)(11). Also, several studies have shown the crucial role of the L-type/Cav1 phosphorylation in important physiological functions, like the fight or flight response (12)(13)(14)(15).…”
mentioning
confidence: 99%